Genomic insights into the Ixodes scapularis tick vector of Lyme disease - Monika Gulia-Nuss (Nature Portfolio, 2016)
Ticks transmit a large number of pathogens that cause human diseases. Here, the authors sequence the genome of the tick Ixodes scapularisand uncover expansion of genes associated with parasitic processes unique to ticks and tick-host interactions.